THE CORRELATION BETWEEN STUDENTS’ INTEREST IN ENGLISH TEACHING TOPICS AND THEIR LEARNING ACHIEVEMENT AT SMA N 1 2X11 ENAM LINGKUNG - Riyana Apalda; Eliza Eliza; Genta Sakti; Absharini Kardena (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study was conducted to find out the correlation between students’ interest in English teaching topics and their learning achievement at 11th grade of SMA N 1 2X11 Enam Lingkung. This study used correlational design. The sample was the XI F 1 and XI F 3 which consisted of 64 students which selected by using cluster random sampling technique. The technique data collection was questionnaire and students’ achievement test scores. The researcher developed 20 statement of questionnaire based on Arlianty (2016) and students’ achievement test scores were from the mid - term test that had been carried out by teacher at school. Analysis the data was using Pearson’s Product Moment. Based on the data analysis conducted, a correlation coefficient of 0.693 was obtained. The magnitude between these variables was moderate because it lies between the interpretation of 0.40 – 0.699. It means that there is a significant correlation between these variables. So, higher students’ interest in English teaching topics are associated with higher their learning achievement, whereas lower students’ interest in English teaching topics corresponds to lower learning achievement.